Identification and immunogenic potential of glycosylphosphatidylinositol-anchored proteins in Paracoccidioides brasiliensis - Relber Aguiar Gonçales; Relber Aguiar Gonçales; Igor Godinho Portis; Thaila Fernanda dos Reis; Luiz Roberto Basso Júnior; Roberto Martinez; Heng Zhu; Maristela Pereira; Célia Maria de Almeida Soares; Paulo Sergio Rodrigues Coelho (Frontiers in Fungal Biology, 2023)
In fungal pathogens the cell wall plays an important role in host-pathogen interactions because its molecular components (e.g., polysaccharides and proteins) may trigger immune responses during infection. GPI-anchored proteins represent the main protein class in the fungal cell wall where they can perform several functions, such as cell wall remodeling and adhesion to host tissues. Genomic analysis has identified the complement of GPI-anchored proteins in many fungal pathogens, but the function has remained unknown for most of them. Here, we conducted an RNA expression analysis of GPI-anchored proteins of Paracoccidioides brasiliensis which causes paracoccidioidomycosis (PCM), an important human systemic mycosis endemic in Latin America. The expression of the GPI-anchored proteins was analyzed by quantitative PCR in both the mycelium and yeast forms. qPCR analysis revealed that the transcript levels of 22 of them were increased in hyphae and 10 in yeasts, respectively, while 14 did not show any significant difference in either form. Furthermore, we cloned 46 open reading frames and purified their corresponding GPI-anchored proteins in the budding yeast. Immunoblot and ELISA analysis of four purified GPI-anchored proteins revealed immune reactivity of these proteins against sera obtained from PCM patients. The information obtained in this study provides valuable information about the expression of many GPI-anchored proteins of unknown function. In addition, based on our immune analysis, some GPI-anchored proteins are expressed during infection and therefore, they might serve as good candidates for the development of new diagnostic methods.